1993
DOI: 10.3133/ofr93329
|View full text |Cite
|
Sign up to set email alerts
|

Mineral resource assessment of undiscovered mineral deposits for selected mineral deposit types in the Kaibab National Forest, Arizona

Abstract: The Kaibab National Forest (KNF), located on the Colorado Plateau, is an area largely devoid of base-and precious-metal mineral deposits. Previous assessment of the Grand Canyon region for uranium deposits suggests that the KNF is in an area with undiscovered uranium resources comparable to the San Juan Basin, historically the most productive uranium area in the United States. Quantitative probabilistic mineral resource assessment in the KNF is only possible for uranium due to the absence of appropriate models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1994
1994
1999
1999

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…This assessment is primarily a compilation of previously reported information about recognized industrial minerals found in the PNF. Most of the industrial minerals noted here are also described in assessments of the Coconino National Forest and Kaibab National Forest (Bliss, 1993(Bliss, , 1997.…”
Section: Prefacementioning
confidence: 91%
See 3 more Smart Citations
“…This assessment is primarily a compilation of previously reported information about recognized industrial minerals found in the PNF. Most of the industrial minerals noted here are also described in assessments of the Coconino National Forest and Kaibab National Forest (Bliss, 1993(Bliss, , 1997.…”
Section: Prefacementioning
confidence: 91%
“…A new geologic map for the PNF is in preparation by other USGS geologists but is not available at this time. Simplified geologic maps as in Bliss (1993) were not done for this report following the recommendations of Liz Matthews (Forest Service, Flagstaff, verbal commun., 1997) who indicated that existing geologic maps would be used. However, a location map ( fig.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The same strategy used here has been previously used by Finch and others (1990) to give the the uranium endowment for the Grand Canyon, Williams, Flagstaff, Marble Canyon, and Holbrook 1° x 2° quadrangles. The Kaibab National Forest was also assessed the same way (Bliss and Pierson, 1993). The following types of areas may be classified in the CNF; the codes, with the exception of NP and V, are the same as in Finch and others (1990 Areas covered with basalt include B and C (designated as B(b) and C(b)).…”
Section: Previous Assessmentmentioning
confidence: 99%